2012
DOI: 10.1038/lsa.2012.10
|View full text |Cite
|
Sign up to set email alerts
|

Hardfacing steel with nanostructured coatings of Stellite-6 by supersonic laser deposition

Abstract: The ability to manufacture coatings is critical to engineering design. Many components require the application of additional layers to enhance mechanical properties and protect against hostile environments. Supersonic laser deposition (SLD) is a novel coating method based on cold spray (CS) principles. In this technique, the deposition velocities can be significantly lower than those required for effective bonding in CS applications. The addition of laser heat energy permits a change in the thermodynamic exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…In the SLD process, laser is used to heat the deposition zone in order to soften both substrate and powder particles thus allowing the formation of a coating at a much reduced impact velocity [29,30]. Luo et al [31,32] and Lupoi et al [33] studied the wear resistance of Stellite 6 coatings deposited by LC and SLD, the results showed that the properties of the SLD layers of Stellite 6 were superior to those of their conventionally manufactured counterparts. Although SLD technique has been proposed for depositing hard materials, the SLD process has not been well studied, in particular, the performance and characteristics of the coatings of hard and low melting point Ni-based alloys.…”
Section: Introductionmentioning
confidence: 95%
“…In the SLD process, laser is used to heat the deposition zone in order to soften both substrate and powder particles thus allowing the formation of a coating at a much reduced impact velocity [29,30]. Luo et al [31,32] and Lupoi et al [33] studied the wear resistance of Stellite 6 coatings deposited by LC and SLD, the results showed that the properties of the SLD layers of Stellite 6 were superior to those of their conventionally manufactured counterparts. Although SLD technique has been proposed for depositing hard materials, the SLD process has not been well studied, in particular, the performance and characteristics of the coatings of hard and low melting point Ni-based alloys.…”
Section: Introductionmentioning
confidence: 95%
“…At lower laser energy density of F = 0.07 J cm −2 , subwavelength nanofringes, which are always called laser-induced periodic surface structure (LIPSS), can be fabricated on the surface of sample. The mean period of nanofringes is about 530 nm which is smaller than laser wavelength (800 nm), [ 35 ] as shown in Figure 2 a. For linearly polarized incident laser light, the possible physical mechanisms of the nanofringes formation has been given as due to the interference between the incident laser light wave and the excited surface plasmon wave.…”
Section: Doi: 101002/admi201500058mentioning
confidence: 98%
“…Matthew et al [8,9] successfully combined laser cladding with cold spraying together to prepare high-density coatings consisting of Ti and Ti alloy, and used cold N 2 as a carrier gas to reduce the cost of cold spraying. The supersonic laser deposition (SLD) method offers many advantages by combining laser with cold spraying, in particular, the use of a laser to control the deposition temperature, which allows hard materials, such as Stellite 6 and carbide [10,11], to be deposited while maintains the key advantages offered by solid-state cold spraying and replaces high cost helium with nitrogen. Moreover, the high-speed impact of particles on the substrate produces severe plastic deformation, resulting in a good bonding of the coating and the substrate.…”
Section: Introductionmentioning
confidence: 99%